Нейрофізіологічні механізми лікувальної дії. Метода програмованої (керованої) сенсорної депривації = Neurophysiological mechanisms of therapeutic action. Method programmable (manageable) sensory deprivation - Gozhenko, A. I.; Коrshnyak, V. A.; Nаsibullin, B. A. (Journal of Education, Health and Sport, 2016)
Gozhenko А. І., Коrshnyak V. А., Nasibullin B. А. Нейрофізіологічні механізми лікувальної дії. Метода програмованої (керованої) сенсорної депривації = Neurophysiological mechanisms of therapeutic action. Method programmable (manageable) sensory deprivation. Journal of Education, Health and Sport. 2016;6(6):395-404. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55834 http://ojs.ukw.edu.pl/index.php/johs/article/view/3591 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016. НЕЙРОФІЗІОЛОГІЧНІ МЕХАНІЗМИ ЛІКУВАЛЬНОЇ ДІЇ МЕТОДА ПРОГРАМОВАНОЇ (КЕРОВАНОЇ) СЕНСОРНОЇ ДЕПРИВАЦІЇ А. І. Гоженко1, В. А. Коршняк2, Б. А. Насібуллін3 1 ДП "Український НДІ медицини транспорту МОЗ України", (м. Одеса) 2 ДУ "Інститут неврології, психіатрії та наркології НАМН України", (м. Харків) 3 ДУ "Український НДІ медичної реабілітації та курортології", (м. Одеса) Резюме Життєдіяльність будь-якого організму передбачає, перед усім, вирішення двох проблем: перша - пристосування до навколишнього середовища (адаптація); друга – збереження оптимальних параметрів біохімічних, фізіологічних та інших механізмів в межах великої відкритої системи, якою є організм. Для людини необхідним супроводженням взаємодії з навколишнім середовищем є психоемоційна оцінка значення подій і явищ, з якими він стикається. У попередніх роботах автори встановили, що застосування методу сенсорної депривації по відношенню до хворих з астено-невротичними розладами суттєво покращує збалансованість дії надсегментарних структур вегетативної системи. В умовах сенсорної деривації спостерігали відновлення збалансованості діяльності симпатичного та парасимпатичного відділів ВНС, встановлено високу позитивну ефективність сенсорної депривації в коригуванні стрес-обумовлених пошкоджень діяльності організму, в тому числі і астено-невротичних розладів, це обумовлено тим, що знижуються потоки сенсорної імпульсації від рецепторів зовнішнього спостереження. Ключові слова: нейрофізіологічні механізми, психоемоційна оцінка, сенсорна депривація. Neurophysiological mechanisms of therapeutic action METHOD programmable (manageable) sensory deprivation А. І. Gozhenko1, V. А. Коrshnyak2, B. А. Nasibullin3 1Ukrainian Scientific and Research Institute of Transport Medicine, Odesa 2Institute of Neurology, Psychiatry and Narcology AMS of Ukraine, Kharkiv 3Ukrainian Scientific-Research Institute of Medical Rehabilitation and Balneology of Health of Ukraine, Odesa Resume Vital activity of any organism involves, first of all, to solve two problems: first - adaptation to the environment (adaptation); second - maintaining optimum parameters of biochemical, physiological and other mechanisms within the large open system, which is the body. For a person accompanying the necessary interaction with the environment is the evaluation of psycho-emotional significance of events and phenomena with which he is confronted. In previous studies the authors found that the use of the method of sensory deprivation with respect to patients with asthenic-neurotic disorders significantly improves balance action suprasegmental structures of the autonomic system. In terms of sensory derivation watched restore balance of sympathetic and parasympathetic divisions ANS, found high positive effectiveness of sensory deprivation to adjust the stress caused by the damage of the body, including asthenic-neurotic disorders, it is because the reduced flow of sensory impulses from the receptors outside observation. Keywords: neurophysiological mechanisms psycho-emotional assessment, sensory deprivation.